Common and different roles of IL-4 and IL-13 in skin allergy and clinical implications. Issue 4 (August 2019) - Roesner, Lennart M.; Zeitvogel, Jana; Heratizadeh, Annice
Abstract : Purpose of review: This review summarizes the mode of action of IL-4 and IL-13 in skin allergy, upcoming therapeutics and depicts key outcomes of the latest clinical trials. Recent findings: Atopic dermatitis is considered to be one of the most common inflammatory skin disease in industrialized countries. Accompanied by strong pruritus, atopic dermatitis has a significant impact on quality of life in severely affected individuals. Aside from unspecific immunosuppressant medications, therapeutics targeting the key cytokines IL-4 and IL-13 and their downstream mediators are under development or have been approved just recently with outstanding potential. Summary: The recent development of several biologics and small compounds has the potential to revolutionize the treatment of atopic dermatitis, and applying this set of state-of-the-art drugs will provide a unique chance to gain insights into this skin disorder, patient subgroups, and key inflammatory mediators.